Pengaruh Kompetensi Terhadap Kinerja Pegawai Pada Dinas â€œXâ€Kabupaten Bengkalis - Rahmat, Yogie (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
Performance is the result or level of success of an individual in carrying out tasks compared to various possibilities, such as work standards, targets, or predetermined and mutually agreed criteria. The objective of this research is to determine the Influence of Competence on Employee Performance in the